ChemInform Abstract: Cu‐Catalyzed Direct Cyanation of Terminal Alkynes with AMBN or AIBN as the Cyanation Reagent. Issue 2 (23rd December 2015) - Rong, Guangwei; Mao, Jincheng; Zheng, Yang; Yao, Ruwei; Xu, Xinfang
Abstract: The title reaction has a broad substrate scope, thus providing aryl, hetaryl, and alkylpropionitriles, and is applicable to diynes.